Early fibroproliferative signs on high-resolution CT are associated with mortality in COVID-19 pneumonia patients with ARDS: a retrospective study - Zhilin Zeng; Min Xiang; Hanxiong Guan; Yiwen Liu; Huilan Zhang; Liming Xia; Juan Zhan; Qiongjie Hu (SAGE Publishing, 2021)
Objectives: To investigate the chest high-resolution computed tomography (HRCT) findings in coronavirus disease 2019 (COVID-19) pneumonia patients with acute respiratory distress syndrome (ARDS) and to evaluate its relationship with clinical outcome. Materials and methods: In this retrospective study, 79 COVID-19 patients with ARDS were recruited. Clinical data were extracted from electronic medical records and analyzed. HRCT scans, obtained within 3 days before clinical ARDS onset, were evaluated by three independent observers and graded into six findings according to the extent of fibroproliferation. Multivariable Cox proportional hazard regression analysis was used to assess the independent predictive value of the computed tomography (CT) score and radiological fibroproliferation. Patient survival was determined by Kaplan-Meier analysis. Results: Compared with survivors, non-survivors showed higher rates of lung fibroproliferation, whereas there were no significant differences in the area of increased attenuation without traction bronchiolectasis or bronchiectasis. A HRCT score <230 enabled the prediction of survival with 73.5% sensitivity and 93.3% specificity, 100% negative predictive value (NPP), 83.3% positive predictive value (PPV) and 88.6% accuracy (Area Under the Curve [AUC] = 0.9; 95% confidence Interval [CI] 0.831-0.968). A multivariate Cox proportional hazards model showed that the HRCT score is a significant independent risk factor for mortality (Hazard Ratio [HR] 9.94; 95% CI 4.10-24.12). Kaplan-Meier analysis revealed that a HRCT score ⩾230 was associated with a higher fatality rate. Organ injury occurred less frequently in patients with a HRCT score <230 compared to those with a HRCT score ⩾230. Conclusion: Early pulmonary fibroproliferative signs on HRCT are associated with increased mortality and susceptibility to organ injury in COVID-19 pneumonia patients with early ARDS.